Development of a disaster kit based on a cultural context for flood disaster relief and preparedness - Nurumal, Mohd Said; Aung, Khin Thandar; A., Wan Nurizzati (International Islamic University Malaysia, 2019)
Introduction: Flood disaster is a natural disaster that has unexpectedly occurred again. Community cooperation in terms of managing flood and focusing on families’ needs has become more systematic. It is important for a household to be prepared in any disaster. One of the preparations that should be done is the stockpiling of emergency supplies or flood supply kits during evacuation. This study aimed to develop a specific disaster kit for households for evacuation during a flood disaster based on cultural context. Methods: Data were collected from 75 key informants from every level of households that really have a great experience during the flood disaster that helping family packing for a living needs before evacuation. The development of the disaster kit based on cultural needs and all their views, needs, experiences, challenges, frustration and happiness was obtained from the interview sessions. Results: There are five themes that emerged from this research related to developing a disaster kit. The themes are community preparedness in dealing with flood disaster, hygiene issues during the flood, inadequate food supply, how the community responds to insufficient water supply, and coping method with illness. After being finalized, there are seven kits: a general supplies kit, documentation kit, emergency food and water supply kit, prayer kit, hygiene kit, basic first aid kit, and baby kit. Conclusion: The development disaster kit was created to help the communities to be more aware and prepared before disaster strikes